Physical activity and Lynch syndrome - Chakraborty, Susmita (2018)
Physical activity promotes health and well-being of an individual. It may help to reduce the onset of various chronic diseases such as diabetes, cardiovascular diseases, and cancer. This study is a part of the research project called “Lynch syndrome and lifestyle” by Central Finland Health Care District and the University of Jyväskylä. Lynch syndrome or Hereditary Nonpolyposis Colorectal Cancer (HNPCC) is caused by an inherited mutation of mismatch repair genes and is associated with increased risk of developing cancer in one’s lifetime. The purpose of this study is to analyze the physical activity profile of people with Lynch syndrome in Finland. Additionally, it investigates the association between physical activity and cancer in people with Lynch syndrome. According to the Lynch syndrome registry in Finland, the questionnaires were sent to 952 family members with Lynch syndrome. Total 414 participants responded. Among them 47% participants have cancer and 53% do not have cancer. The data were analyzed by independent t-test, chi-square test and logistic regression using IBM SPSS statistics. The study found an association between current physical activity and cancer occurrence (odds ratio [OR] 2.71, 95% confidence interval [CI] 1.50−4.92). About two-thirds of the participants with Lynch syndrome have meet WHO physical activity guidelines from both groups (cancer and without cancer). The study indicated a statistically significant difference of current physical activity between cancer and without cancer people with Lynch syndrome (𝑝=0.008). Apart from considerable health benefits, physical activity can aid to spread the knowledge of Lynch syndrome among young people. Very few studies have observed the influence of physical activity on the development of cancer in people with Lynch syndrome. This study has a high potential for further research on physical activity, evidence-based guidance, and hereditary cancer. Furthermore, the study findings would add value for physical activity promotion among Lynch syndrome families.